PI3K activation in neural stem cells drives tumorigenesis which can be ameliorated by targeting the cAMP response element binding protein - Daniel, P.; Filiz, G.; Brown, D.; Christie, M.; Waring, P.; Zhang, Y.; Haynes, J.; Pouton, C.; Flanagan, D.; Vincan, Elizabeth; Johns, T.; Montgomery, K.; et al. (OXFORD UNIV PRESS INC, 2018)
© The Author(s) 2018. Background. Hyperactivation of phosphoinositide 3-kinase (PI3K) signaling is common in cancers, but the precise role of the pathway in glioma biology remains to be determined. Some understanding of PI3K signaling mechanisms in brain cancer comes from studies on neural stem/progenitor cells (NSPCs), where signals transmitted via the PI3K pathway cooperate with other intracellular pathways and downstream transcription factors to regulate critical cell functions. Methods. To investigate the role of the PI3K pathway in glioma initiation and development, we generated a mouse model targeting the inducible expression of a PIK3CAH1047A oncogenic mutant and deletion of the PI3K negative regulator, phosphatase and tensin homolog (PTEN), to NSPCs. Results. Expression of a Pik3caH1047A was sufficient to generate tumors with oligodendroglial features, but simultaneous loss of PTEN was required for the development of invasive, high-grade glioma. Pik3caH1047A-PTEN mutant NSPCs exhibited enhanced neurosphere formation which correlated with increased Wnt signaling, while loss of cAMP response element binding protein (CREB) in Pik3caH1047A-Pten mutant tumors led to longer symptom-free survival in mice. Conclusion. Taken together, our findings present a novel mouse model for glioma demonstrating that the PI3K pathway is important for initiation of tumorigenesis and that disruption of downstream CREB signaling attenuates tumor expansion.